Caracterización de polimorfismos genéticos en la región AZF del cromosoma Y potencialmente asociados a infertilidad en distintos grupos étnicos de la población argentina actual - Alechine, Evguenia (2014)
Microdeletions in the AZF region of the Y chromosome are routinely analyzed in azoospermic and severe oligozoospermic patients, in order to predict sperm recovery by testicular biopsies. Several population studies have shown variation in the prevalence and effect of these microdeletions. Aiming to characterize the Argentinean population, 240 fertile men belonging to haplogroup Q3, 170 infertile and 90 azoospermic patients have been analyzed. Our results discarded the existence of constitutive microdeletions in haplogroup Q3, as well as the association between partial deletions and sperm count decrease. The prevalence of complete microdeletions was 11.1%, being only correlated with severe sperm count alterations, regardless of the patient?s haplogroup. Conversely, certain haplogroups showed association with partial deletions without any pathogenic effect. Only deletions of AZFbc and AZFabc regions evidenced complete absence of spermatogenesis in the testis. The existence of azoospermic patients without microdeletions suggests that other factors could be affecting spermatogenesis. Given that it is not possible to predict sperm recovery by analyzing only the currently suggested markers, the present work concluded with the development of a molecular biology tool for the detection of spermatogenesis candidate genes. The identification of novel markers will allow a better diagnosis and genetic counselling for the infertile couple.